Comparative politics of Southeast Asia: an introduction to governments and political regimes - Croissant, Aurel (Springer International Publishing, 2022)
Chapter 1. Government and Political Regimes in Southeast Asia: An Introduction -- Chapter 2. Brunei Darussalam: Malay Islamic Monarchy and Rentier State -- Chapter 3. Cambodia: From UN-Led Peace-Building to Post-genocidal Authoritarianism -- Chapter 4. Indonesia: Challenges of Conflict and Consensus in the Era of Reformasi -- Chapter 5. Laos: The Transformation of Periphery Socialism -- Chapter 6. Malaysia: Competitive Authoritarianism in a Plural Society -- Chapter 7. Myanmar: Political Conflict and the Survival of the Praetorian State -- Chapter 8. Philippines: People's Power and Defective Elite Democracy -- Chapter 9. Singapore: Contradicting Conventional Wisdom About Authoritarianism, State and Development -- Chapter 10. Thailand: The Vicious Cycle of Civilian Government and Military Rule -- Chapter 11. Timor-Leste: Challenges of Creating a Democratic and Effective State -- Chapter 12. Vietnam: The Socialist Party-State -- Chapter 13. Comparing Governments and Political Institutions in Southeast Asia -- Chapter 14. Democracy and Dictatorship in Southeast Asia – Retrospective and Prospective.
Keywords: Association of Southeast Asian Nations; Osttimor